Empirical Testing of Purchasing Power Parity Validity in Selected European Union Countries - Jelko Plošinjak; Mejra Festić (Naše gospodarstvo/Our economy, 2021)
In this article, the authors carried out an empirical analysis of the validity of purchasing power parity (PPP) in Slovenia, Croatia, the Czech Republic, Slovakia and Austria. The results provide mixed support for PPP, which is typical for ex- transition economies. In the first phase of the empirical part of the research, the authors tested the stationarity of the real exchange rate in a logarithm, while in the second phase, the cointegration of nominal exchange rate, domestic and foreign price levels was tested.The Vector Error Correction Model (VECM) was used in the third phase to test if the signs of variables are in accordance with economics and econometrics theories, while in the final phase, restrictions were imposed for the symmetry and proportionality of coefficients. Slovenia is subject to limitations on the symmetry and proportionality of coefficients, which means the validity of both the absolute and relative versions of the PPP theory. Croatia is subject to a limitation on symmetry, but not to a limit on the proportionality of coefficients, which means the validity of the relative version of the PPP theory. In the case of the Czech Republic, Slovakia and Austria, restrictions on the symmetry and proportionality of the coefficients do not apply, which consequently constitutes an invalidity of both versions. However, to the authors' knowledge, and taking into account Liu (1992), who states that it is more important to check the presence of co-integration than to check the symmetry and proportionality of the coefficients, since there is a co- integratation between the nominal exchange rate, foreign prices and domestic prices, the theory of PPP is valid for all the selected countries. The empirical results suggest that all the real exchange rate time series are stationary, additionally, cointegration exists among all the variables for all countries, and the signs of coefficients are statistically significant for all variables in all countries, however, the coefficient restrictions are only statistically significant in Slovenia and Croatia.